1991
DOI: 10.1016/0014-5793(91)80705-8
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomes occurring in protein‐free hybridoma cell culture Evidence for programmed cell death

Abstract: In addition to monoclonat immunogtobutin. two kinds of nuctcoproteins. NPI and NP?. were isolated from the supernatants of hybridoma cultures set up in a protein-free medium. As shown by SDS-etectrophorcsis the two nucleoprotcins shared a set of proteins (apparent M, I IO00 to 15000). and differed in the DNA moiety ( 4 150 bp in NP I. -350 bp in NP2). The amino acid composition of the protein moiety confirmed the nucteosomal origin of NPI and NP2. The findings support the view that in hybridoma cultures the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 13 publications
4
39
0
1
Order By: Relevance
“…Apoptosis is triggered by a cascade of cysteine proteases called caspases, which are activated in response to various insults that may develop in bioreactors during batch or fed batch cultures. It has been observed that apoptosis is a common mode of cell death in CHO culture, especially in the post-exponential growth phase (Franek and Dolnikova, 1991;Golstein et al, 1991;Goswami et al, 1999).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is triggered by a cascade of cysteine proteases called caspases, which are activated in response to various insults that may develop in bioreactors during batch or fed batch cultures. It has been observed that apoptosis is a common mode of cell death in CHO culture, especially in the post-exponential growth phase (Franek and Dolnikova, 1991;Golstein et al, 1991;Goswami et al, 1999).…”
Section: Motivationmentioning
confidence: 99%
“…As nutrients are depleted and metabolic activity slows down, growth stops and apoptosis is triggered. Apoptosis accounts for the majority of cell death in bioreactors (Franek and Dolnikova, 1991;Golstein et al, 1991;Goswami et al, 1999) and so it significantly impacts cell density and viability, and thus product titer. A major cause for apoptosis in batch culture is likely depletion of vital nutrients such as glucose (Goswami et al, 1999) and amino acids such as glutamine and asparagine (Sanfeliu and Stephanopoulos, 1999;Simpson et al, 1998b).…”
Section: Motivationmentioning
confidence: 99%
“…In cell culture or in ascites, nucleosomes released from dead cells [5] could associate with monoclonal autoantibody to form complexes. Detection of such complexes in MoAb preparations should be carried out to discriminate the effects directly related to the antibody from those mediated by immune complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Изменения на поверхнос ти клеток во время апоптоза (включая экспрессию фосфа-тидилсериновых и тромбоспондиновых рецепторов) приво дят к быстрому фагоцитозу клеток апоптоза макрофагами для предотвращения утечки составных частей воспалитель ных клеток в окружающую микросреду. Однако количест венные и/или качественные различия в апоптозе могут привести к системному высвобождению нуклеосом [11,13]. В циркуляции у больных СКВ ДНК находится в фор ме (олиго)нуклеосом [24].…”
unclassified